Persistent carbon composition converges across vegetated and unvegetated coastal soils despite contrasting stabilization pathways - Yuan Li; Joeri Kaal; Chuancheng Fu; Dongdong Zhang; Peter I. Macreadie; Ting Wang; Lin Zeng; Feilong Hu; Guangxuan Han; Yongming Luo (Water Research, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

A dual-responsive silica-based molecularly imprinted polymer for sustainable and specific adsorption of γ-aminobutyric acid from Moringa oleifera seeds - Jiabo Cheng; Jirui Sui; Xuanyi Yu; Kungang Li; Qi Liang; Chuancheng Lin; Mingxing Li; Chunying Li; Chunjian Zhao (Food Research International, 2026)

Geo-mechanical Model Test on Strong Mine Tremors Induced by the Breakage of High Thick-and-Hard Overlying Strata During Longwall Coal Retreat Mining - Hanxiang Lin; Qiangyong Zhang; Kang Duan; Pengfei Wang; Xiufeng Zhang; Chuancheng Liu; Changpeng Chen; Yu Zhao (Rock Mechanics and Rock Engineering, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

Losses and destabilization of soil organic carbon stocks in coastal wetlands converted into aquaculture ponds - Shaoying Lin; Yaxin Zhou; Weiqi Wang; Jordi Sardans; Yuan Li; Chuancheng Fu; Fanjiang Zeng; Zhaoliang Song; Akash Tariq; Josep Peñuelas (Global Change Biology, 2024)
Coastal‐wetlands play a crucial role as carbon (C) reservoirs on Earth due to their C pool composition and functional sink, making them significant for mitigating global climate change. However, due to the development and utilization of wetland resources, many wetlands have been transformed into other land‐use types. The current study focuses on the alterations in soil organic‐C (SOC) in coastal‐wetlands following reclamation into aquaculture ponds. We conducted sampling at 11 different coastal‐wetlands along the tropical to temperate regions of the China coast. Each site included two community types, one with solely native species ( Suaeda salsa , Phragmites australis and Mangroves) and the other with an adjacent reclaimed aquaculture pond. Across these 11 locations we compared SOC stock, active OC fractions, and soil physicochemical properties between coastal wetlands and aquaculture ponds. We observed that different soil uses, sampling sites, and their interaction had significant effects on SOC and its stock ( p p p

Climate and mineral accretion as drivers of mineral‐associated and particulate organic matter accumulation in tidal wetland soils - Chuancheng Fu; Yuan Li; Lin Zeng; Chen Tu; Xiaoli Wang; Haiqing Ma; Leilei Xiao; Peter Christie; Yongming Luo (Global Change Biology, 2024)
Tidal wetlands sequester vast amounts of organic carbon (OC) and enhance soil accretion. The conservation and restoration of these ecosystems is becoming increasingly geared toward “blue” carbon sequestration while obtaining additional benefits, such as buffering sea‐level rise and enhancing biodiversity. However, the assessments of blue carbon sequestration focus primarily on bulk SOC inventories and often neglect OC fractions and their drivers; this limits our understanding of the mechanisms controlling OC storage and opportunities to enhance blue carbon sinks. Here, we determined mineral‐associated and particulate organic matter (MAOM and POM, respectively) in 99 surface soils and 40 soil cores collected from Chinese mangrove and saltmarsh habitats across a broad range of climates and accretion rates and showed how previously unrecognized mechanisms of climate and mineral accretion regulated MAOM and POM accumulation in tidal wetlands. MAOM concentrations (8.0 ± 5.7 g C kg −1 ) (±standard deviation) were significantly higher than POM concentrations (4.2 ± 5.7 g C kg −1 ) across the different soil depths and habitats. MAOM contributed over 51.6 ± 24.9% and 78.9 ± 19.0% to OC in mangrove and saltmarsh soils, respectively; both exhibited lower autochthonous contributions but higher contributions from terrestrial or marine sources than POM, which was derived primarily from autochthonous sources. Increased input of plant‐derived organic matter along the increased temperature and precipitation gradients significantly enriched the POM concentrations. In contrast, the MAOM concentrations depended on climate, which controlled the mineral reactivity and mineral–OC interactions, and on regional sedimentary processes that could redistribute the reactive minerals. Mineral accretion diluted the POM concentrations and potentially enhanced the MAOM concentrations depending on mineral composition and whether the mineral accretion benefited plant productivity. Therefore, management strategies should comprehensively consider regional climate while regulating sediment supply and mineral abundance with engineering solutions to tap the OC sink potential of tidal wetlands.

An overlooked soil carbon pool in vegetated coastal ecosystems: National-scale assessment of soil organic carbon stocks in coastal shelter forests of China - Yuan Li; Chuancheng Fu; Weiqi Wang; Lin Zeng; Chen Tu; Yongming Luo (Science of The Total Environment, 2023)

Stocks and losses of soil organic carbon from Chinese vegetated coastal habitats - Chuancheng Fu; Yuan Li; Lin Zeng; Haibo Zhang; Chen Tu; Qian Zhou; Kuanxu Xiong; Jiaping Wu; Carlos M. Duarte; Peter Christie; Yongming Luo (Global Change Biology, 2021)
Global vegetated coastal habitats (VCHs) represent a large sink for organic carbon (OC) stored within their soils. The regional patterns and causes of spatial variation, however, remain uncertain. The sparsity and regional bias of studies on soil OC stocks from Chinese VCHs have limited the reliable estimation of their capacity as regional and global OC sinks. Here, we use field and published data from 262 sampled soil cores and 181 surface soils to report estimates of soil OC stocks, burial rates and losses of VCHs in China. We find that Chinese mangrove, salt marsh and seagrass habitats have relatively low OC stocks, storing 6.3 ± 0.6, 7.5 ± 0.6, and 1.6 ± 0.6 Tg C (±95% confidence interval) in the top meter of the soil profile with burial rates of 44 ± 17, 159 ± 57, and 6 ± 45 Gg C/year, respectively. The variability in the soil OC stocks is linked to biogeographic factors but is mostly impacted by sedimentary processes and anthropic activities. All habitats have experienced significant losses, resulting in estimated emissions of 94.2–395.4 Tg CO 2 e (carbon dioxide equivalent) over the past 70 years. Reversing this trend through conservation and restoration measures has, therefore, great potential in contributing to the mitigation of climate change while providing additional benefits. This assessment, on a national scale from highly sedimentary environments under intensive anthropogenic pressures, provides important insights into blue carbon sink mechanism and sequestration capacities, thus contributing to the synchronous progression of global blue carbon management.